2012
DOI: 10.1111/jpm.12020
|View full text |Cite
|
Sign up to set email alerts
|

Productive Ward initiative promotes better communication between mental health teams and ensures timely discharge for patients

Abstract: The Productive Ward is an initiative whereby nursing staff are empowered to bring about changes in the workplace to streamline systems and release time to care for patients. It is an evidence-based approach, which brings about improved clinical and safety outcomes. This paper discusses how three of the Productive Ward Modules - Ward Round, Admissions and Planned Discharge, and Patient Status At a Glance - have meshed to promote better communication and working between inpatient nursing and medical teams, Home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In comparing these results with previous findings, other implementations of Productive Series programmes have been reported to generate various improvements (e.g. Dean, 2014;Lennard, 2014;Lipley, 2009), and similarly in this implementation, staff reported benefits such as improved stock control, time management, and use of Electronic Patient Records. Although the existing literature focuses less on the challenging aspects of the programme, in a national web-survey of frontline staff (n = 150), National Nursing Research Unit and NHS Institute for Innovation and Improvement (2010b) identified some of the barriers to implementation which had similarities with the issues identified in this study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In comparing these results with previous findings, other implementations of Productive Series programmes have been reported to generate various improvements (e.g. Dean, 2014;Lennard, 2014;Lipley, 2009), and similarly in this implementation, staff reported benefits such as improved stock control, time management, and use of Electronic Patient Records. Although the existing literature focuses less on the challenging aspects of the programme, in a national web-survey of frontline staff (n = 150), National Nursing Research Unit and NHS Institute for Innovation and Improvement (2010b) identified some of the barriers to implementation which had similarities with the issues identified in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, a Senior Associate at the NHS Institute for Innovation and Improvement, (Manning, 2011) promotes the Productive Community Services, referring to improvements such as a 48% reduction in stock held for a school nursing team. Productive Ward has also been associated with increased quality of patient observations and patient satisfaction (Lipley, 2009), increased staff satisfaction (Dean, 2014;Wright et al, 2012), increased Direct Care Time with patients (Blakemore, 2009), the reduction of hospital-acquired infections (Foster et al, 2009;Smith and Rudd, 2010) staff sickness (Smith and Rudd, 2010), and falls (Wilson, 2009), and more efficient admission and discharge processes (Lennard, 2014). Few of these articles provide much detail regarding the negative aspects of the programme's implementation, although for an exception see Wright et al (2012), who notes that implementing just the first module cost £236 per meeting in staff time before accounting for the time taken to prepare data and carry out the module work.…”
Section: Introductionmentioning
confidence: 99%
“…This approach relies upon continuous quality improvement of the production processes to achieving perfection, with accountability resting with the people at the point of service (Bercaw, 2013). Although there is evidence of a reduction in resources around care processes (Davis and Adams, 2012;Lennard, 2014), there are arguments against it with demonstrated increases in documentation and auditing, and actual time at the bedside remaining either unchanged or even reduced (Brackett et al, 2013).…”
Section: Organisational Influencesmentioning
confidence: 99%
“…Second, those that describe its adoption, implementation and level of engagement in a particular context or locality 12–16. And finally, those that describe reported outcomes from the programme 17–22. The majority report benefits of the programme at both staff and patient levels, while others indicate that data support an increase in patient contact time 22–24.…”
Section: Introductionmentioning
confidence: 99%